2022
DOI: 10.14740/jmc4008
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-Induced Myasthenia Gravis and Myositis: Literature Review on Neurological Toxicities of Programmed Death Protein 1 Inhibitors

Abstract: We present herein the case of an elderly male patient, who was receiving immunotherapy for his urothelial cancer and who presented to our facility with lower extremity weakness. The patient was diagnosed with myasthenia gravis, thyroiditis, myositis and myocarditis, which were considered as immune adverse events of pembrolizumab therapy. The patient received pyridostigmine, intravenous immunoglobulin, plasmapheresis, corticosteroids, and rituximab with mild improvement of his symptoms. The patient had some neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…irAEs can affect any organ system, and their severity can range from mild to life-threatening. Common irAEs include pneumonitis, colitis, hepatitis, endocrinopathies, and dermatitis [ 4 , 7 ]. The incidence of irAEs with pembrolizumab is higher than with other immune checkpoint inhibitors, possibly due to its higher affinity for PD-1 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…irAEs can affect any organ system, and their severity can range from mild to life-threatening. Common irAEs include pneumonitis, colitis, hepatitis, endocrinopathies, and dermatitis [ 4 , 7 ]. The incidence of irAEs with pembrolizumab is higher than with other immune checkpoint inhibitors, possibly due to its higher affinity for PD-1 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms of action have implications for rheumatology and other autoimmune diseases [ 13 ]. Hydroxychloroquine has been shown to induce MG on its own, as has pembrolizumab [ 7 , 14 ]. While we do not believe that the patient’s MG was triggered by hydroxychloroquine alone, as she had been taking this for the long term, it could be that an interaction between the immunomodulatory effects of both hydroxychloroquine and pembrolizumab occurs.…”
Section: Discussionmentioning
confidence: 99%
“…One study found an incidence of high-grade (Grade 3-4) irAE, including myasthenic syndromes, was less than 1% in patients receiving immune checkpoint inhibitors (ICI) [6]. Myasthenia gravis [7][8][9][10][11], encephalitis/meningitis [12], inflammatory polyradiculopathies [13] such as Guillain-Barre syndrome, and peripheral neuropathy have been described most commonly [14]. The significance of these associated neurological disorders resides in their high mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, immune checkpoint inhibitors are not void of adverse effects, including autoimmune toxicity caused by the risk of activated T lymphocytes attacking normal tissue generally known as immune-related adverse events (irAEs) that could affect the skin, gastrointestinal tract, liver, and endocrine system among other organ and tissues [5]. Furthermore, ICIs have been linked to a wide spectrum of neurologic immune-related adverse events (irAEs), including meningoencephalitis, myasthenia gravis, and various neuropathies, as well as endocrinology systems such as hypo-or hyperthyroidism [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%